(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
A new methodology to manufacture mucosal membrane contact Covid-19 diagnostic items using powder-bed Additive Manufacturing (AM) and vapor smoothing methods was developed and introduced to fulfill the population testing demand. The technique can rapidly manufacture oral/respiratory diagnostic items at the point of use and at scale. Surface medical device tests were performed to evaluate biocompatibility of such Additively Manufactured Covid-19 diagnostic items. The presented results are the most in-depth medical study of vapor smoothed Additively Manufactured medical articles to date.